Afterload reduction: a comparison of captopril and nifedipine in dilated cardiomyopathy. Issue 4 (April 1986) - Agostoni, P G; De Cesare, N; Doria, E; Polese, A; Tamborini, G; Guazzi, M D
Abstract : Nifedipine and captopril are potent vasodilators and may be expected to help left ventricular failure by reducing afterload. Nifedipine (20 mg three times a day) and captopril (50 mg three times a day) were added to an optimal regimen of digitalis and diuretics in a double blind crossover trial in 18 cases of dilated cardiomyopathy. New York Heart Association functional class rating symptoms and exercise tolerance times improved on captopril but not on nifedipine. The reduction in pulmonary capillary wedge pressure and the increase of cardiac output on captopril indicated that the augmented functional capacity may have resulted in part from an improved performance of the left ventricle. Although there were comparable decreases in systemic vascular resistance and presumably in impedence to ejection by the left ventricle on both drugs, the dimensions of the ventricular cavity were found to be reduced by captopril and augmented by nifedipine, and only captopril reduced the afterload (wall stress). In addition, the force-length relation (between left ventricular end systolic stress and end systolic diameter) was shifted to the left of baseline by captopril and to the right by nifedipine, suggesting that muscle contractility was reduced by nifedipine and not by captopril. These results suggest that nifedipine and captopril have different effects on afterload and contractility and these may account for the different effects of these drugs on the performance of the heart and clinical responses.